The age of low tech : towards a technologically sustainable civilization - Bihouix, Philippe (Bristol University Press, 2020)
A best-seller in France, this English language edition introduces readers to an alternative perspective on our technological future. Bihouix skilfully goes against the grain to argue that 'high' technology will not solve global problems and envisages a different approach to manage our resources and build a more resilient and sustainable society